An Analysis of Omission in Students’ English Writings - Ingatan Gulö; Teo Vany Rahmawelly (Universitas Teknokrat Indonesia, 2018)
This paper is part of research with a larger scope covering errors students made related to subject-verb agreement. This part aims to elaborate grammatical problems faced by foreign language learners of English in relation to the omission they made in their writings. A qualitative data collection method was applied in gathering the data. The researchers collected pieces of writing from the students, read them, and analysed the omission errors found in the collected writings. As result, the most common omissions found in the data are related to verb markers. Omission of main verbs and auxiliaries also occur, creating sentences without any verbs or grammatically necessary auxiliaries. Absense of these kinds of function in Indonesian is the main reason for this grammatical problem faced by the learners. In addition, omissios of suffix -ing were also found by the researchers in the data. These findings should be able to contribute to existing works on grammatical errors and increase the success of both teaching and learning of a foreign language like English.Key Words: error, grammar, omission, writing